Quality costs monitoring - pilot project in lasselsberger´s production plant - Hyršlová, Jaroslava; Bednaříková, Marie; Tesnerová, Patricie (Univerzita Pardubice, 2010)
The costs of quality play an important role in the management system, as they indicate the level of management in relation to quality, reveal potential possibilities for savings and help to raise the effectiveness of the decision-making in the area of quality management. The aim of this article is to present the pilot project of the quality costs monitoring system in the production plant of a company that produces ceramic tiling. The company is the largest manufacturer of ceramic tiles and paving in the Czech Republic and one of the biggest European manufacturers of tiling materials.
Keywords: monitoring system; costs; Lasselsberger´s production